The Effect of Maintenance Behavior of Orthodontic User's Dental And Mouth Cleanliness with Dental Hygiene Status in SMAN 1 Darul Imarah (Darul Imarah Public High School 1) Aceh Besar Regency - Cut Ratna Keumala; Sisca Mardelita; Andriani (Science Midwifery, 2022)
The prevalence of orthodontic users according to age group, is greatest at the age of 15 years by 1%. This study aims to identify the behavior of orthodontic users in maintenance and to see the differences in the behavior of maintaining oral and dental hygiene of adolescent orthodontic users before and after counseling on dental and oral hygiene maintenance. The method used in this research is analytic by using the T test to see differences in behavior before and after counseling. The sample used is the total population, namely the students of SMAN Darul Imarah who use orthodontics totaling 56 students. The study was carried out with pre and post test group design and performed dental and oral hygiene checks using the PHP-M index before and after counseling. The results showed that there was an increase in knowledge after counseling with a p-value of 0.008, there was a change in attitude with a p-value of 0.001, there was a change in action with a p-value of 0.001 and a PHP-M value for the better which indicates the influence of knowledge, attitudes and actions of adolescent orthodontic users. become better after counseling. From the research and discussion, it can be concluded that there is an effect of dental and oral hygiene maintenance behavior on the oral hygiene of orthodontic adolescent users at SMAN 1 Darul Imarah, Aceh Besar. The attitudes and actions of orthodontic users became better after counseling. From the research and discussion, it can be concluded that there is an effect of dental and oral hygiene maintenance behavior on the oral hygiene of orthodontic adolescent users at SMAN 1 Darul Imarah, Aceh Besar. The attitudes and actions of orthodontic users became better after counseling. From the research and discussion, it can be concluded that there is an effect of dental and oral hygiene maintenance behavior on the oral hygiene of orthodontic adolescent users at SMAN 1 Darul Imarah, Aceh Besar.